Primary adrenal insufficiency is associated with impaired natural killer cell function: a potential link to increased mortality. Issue 4 (April 2017) - Bancos, Irina; Hazeldine, Jon; Chortis, Vasileios; Hampson, Peter; Taylor, Angela E; Lord, Janet M; Arlt, Wiebke
Abstract : Objective: Mortality in patients with primary adrenal insufficiency (PAI) is significantly increased, with respiratory infections as a major cause of death. Moreover, patients with PAI report an increased rate of non-fatal infections. Neutrophils and natural killer (NK) cells are innate immune cells that provide frontline protection against invading pathogens. Thus, we compared the function and phenotype of NK cells and neutrophils isolated from PAI patients and healthy controls to ascertain whether altered innate immune responses could be a contributory factor for the increased susceptibility of PAI patients to infection. Design and methods: We undertook a cross-sectional study of 42 patients with PAI due to autoimmune adrenalitis ( n =  37) or bilateral adrenalectomy ( n =  5) and 58 sex- and age-matched controls. A comprehensive screen of innate immune function, consisting of measurements of neutrophil phagocytosis, reactive oxygen species production, NK cell cytotoxicity (NKCC) and NK cell surface receptor expression, was performed on all subjects. Results: Neutrophil function did not differ between PAI and controls. However, NKCC was significantly reduced in PAI (12.0 ± 1.5% vs 21.1 ± 2.6%, P  < 0.0001). Phenotypically, the percentage of NK cells expressing the activating receptors NKG2D and NKp46 was significantly lower in PAI, as was the surface density of NKG2D (all P  < 0.0001). Intracellular granzyme B expression was significantly increased in NK cells from PAI patients ( P  < 0.01). Conclusions: Adrenal insufficiency is associated with significantly decreased NKCC, thereby potentially compromising early recognition and elimination of virally infected cells. This potential impairment in anti-viral immune defense may contribute to the increased rate of respiratory infections and ultimately mortality in PAI.